2009
DOI: 10.1007/s12663-009-0039-2
|View full text |Cite
|
Sign up to set email alerts
|

A study on coronal incision for treating zygomatic complex fractures

Abstract: Objective To study the value of coronal incisions for treating zygomatic complex fractures and evaluate the advantages, indications and complications associated with it. Method In this prospective study, 12 patients were randomly selected regardless of age, sex requiring open reduction and internal fixation of communited zygomatic complex fractures with or without other associated fractures of the midface. Patients were all treated by coronal approach for open reduction and internal fixation of fracture of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“… N/A 5 (62.5) .1 (.3; .06 to .14) vs. g .048 (.2; .04 to .99) vs. h .06 (.24; .05 to 1.1) vs. i Shetty et al . [ 23 ] (2009, India) Staffs, [single-degree/BDS] OMFS 12 (3) 28.7 ± ? (25–40) N/A ?…”
Section: Discussionmentioning
confidence: 99%
“… N/A 5 (62.5) .1 (.3; .06 to .14) vs. g .048 (.2; .04 to .99) vs. h .06 (.24; .05 to 1.1) vs. i Shetty et al . [ 23 ] (2009, India) Staffs, [single-degree/BDS] OMFS 12 (3) 28.7 ± ? (25–40) N/A ?…”
Section: Discussionmentioning
confidence: 99%
“…[15] and Adam et al . [16] who, had a male to female ratio of 4:1 and study conducted on coronal approach for zygomatic complex fracture by Shetty et al .,[17] who had a male to female ratio of 12:0. Road traffic accidents are the major cause of fractures of the upper and middle third facial region (100%).…”
Section: Discussionmentioning
confidence: 99%
“…Shetty et al . [17] reported no case of hematoma in his study of coronal approach for the treatment of the zygomatic complex fractures. Hodges and Altman[14] reported that the use of stabilize drains while closing coronal flap will minimize the complication of hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…This surgical approach has been used by neurosurgeons for over a century [1]. It was originally described in 1907 by Hartley and Kenyon for use in neurosurgical procedures and then adopted by Tessier in craniomaxillofacial surgery in 1970s [1][2][3]. A coronal flap is a versatile flap used by plastics surgery [4], neurosurgery [5] and oral and maxillofacial surgery [2].…”
Section: Introductionmentioning
confidence: 99%